Oxidized Phospholipids in Control of Endothelial Barrier Function: Mechanisms and Implication in Lung Injury - Karki, Pratap; Birukov, Konstantin G. (Frontiers in Endocrinology, 2021)
Earlier studies investigating the pathogenesis of chronic vascular inflammation associated with atherosclerosis described pro-inflammatory and vascular barrier disruptive effects of lipid oxidation products accumulated in the sites of vascular lesion and atherosclerotic plaque. However, accumulating evidence including studies from our group suggests potent barrier protective and anti-inflammatory properties of certain oxidized phospholipids (OxPLs) in the lung vascular endothelium. Among these OxPLs, oxidized 1-palmitoyl-2-arachdonyl-sn-glycero-3-phosphocholine (OxPAPC) causes sustained enhancement of lung endothelial cell (EC) basal barrier properties and protects against vascular permeability induced by a wide variety of agonists ranging from bacterial pathogens and their cell wall components, endotoxins, thrombin, mechanical insults, and inflammatory cytokines. On the other hand, truncated OxPLs cause acute endothelial barrier disruption and potentiate inflammation. It appears that multiple signaling mechanisms triggering cytoskeletal remodeling are involved in OxPLs-mediated regulation of EC barrier. The promising vascular barrier protective and anti-inflammatory properties exhibited by OxPAPC and its particular components that have been established in the cellular and animal models of sepsis and acute lung injury has prompted consideration of OxPAPC as a prototype therapeutic molecule. In this review, we will summarize signaling and cytoskeletal mechanisms involved in OxPLs-mediated damage, rescue, and restoration of endothelial barrier in various pathophysiological settings and discuss a future potential of OxPAPC in treating lung disorders associated with endothelial barrier dysfunction.